Is Digital Animation Superior to Text Resources for Facial Transplantation Education? A Randomized Controlled Trial. Issue 2 (August 2021) - Wolfe, Erin M.; Alfonso, Allyson R.; Diep, Gustave K.; Berman, Zoe P.; Mills, Emily C.; Park, Jenn J.; Hoffman, Alexandra F.; Felsenheld, Julia H.; Ramly, Elie P.; Rodriguez, Eduardo D.
Abstract : Background: Facial transplantation is a complex surgical procedure that requires education of medical professionals, patients, and the general public. The objective of this randomized controlled trial was to compare the educational efficacy of facial transplantation digital animation versus text resources for teaching medical students a complex surgical procedure and its applicable anatomical and surgical principles. Methods: Medical student volunteers were recruited and prospectively randomized to an animation or a text group. Students completed preintervention and postintervention assessments of confidence and knowledge of head and neck anatomy and facial transplantation. Student Evaluations of Educational Quality survey assessed student satisfaction with both tools following study crossover. Knowledge assessment was developed using National Board of Medical Examiners guidelines and content validated by four experts. The Cohen d statistic was used to measure the effect size of each intervention. Results: Thirty-six students were assigned randomly to the animation group ( n = 19) or the text ( n = 17) group. Postintervention analysis demonstrated significantly higher performance scores in the animation group compared to the text group ( p = 0.029). The animation group had a larger effect size (Cohen d = 1.96 versus 1.27). Only students in the animation group reported significantly improved confidence in head and neck anatomy after the intervention ( p = 0.002). Both groups demonstrated significantly increased postintervention confidence in knowledge of facial transplantation ( p < 0.001). Satisfaction scores revealed that students significantly favored the animation resource ( p < 0.001). Conclusions: Animation can be an effective tool for facial transplantation education and results in improved student knowledge, confidence, and satisfaction compared to text resources. Facial transplantation can also be used as an educational framework for teaching medical students anatomical and surgical principles.